2018
DOI: 10.1111/vco.12447
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell populations in lymphoma in dogs and impact of cytotoxic chemotherapy

Abstract: Cancer relapse following chemotherapy has been attributed in part to the presence of cancer stem cells (CSC), which drive tumor growth and metastasis and are highly resistant to the effects of cytotoxic chemotherapy. As a result, treatment with cytotoxic chemotherapy selects for drug-resistant CSC populations that eventually drive tumor recurrence. Little is known currently regarding the role of CSC in dogs with lymphoma, nor the impact of chemotherapy on CSC populations. Therefore, we prospectively quantitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(92 reference statements)
1
1
0
Order By: Relevance
“…Numerous studies have shown the existence of cancer stem-like cells in several types of canine neoplasms [20][21][22][23][24], but few studies have been performed on melanoma [25]. Importantly, our in vitro and in vivo study confirmed the presence of melanoma SCs in canine melanomas.…”
Section: Discussionsupporting
confidence: 75%
“…Numerous studies have shown the existence of cancer stem-like cells in several types of canine neoplasms [20][21][22][23][24], but few studies have been performed on melanoma [25]. Importantly, our in vitro and in vivo study confirmed the presence of melanoma SCs in canine melanomas.…”
Section: Discussionsupporting
confidence: 75%
“…Many studies have proved that there are tumor stem cells in lymphoma [ 4 , 5 ]. Tumor stem cells are highly resistant to radiotherapy and chemotherapy, which is an important mechanism of lymphoma recurrence and metastasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%